THE PROFILE OF PERCENTILE OF FAT OF THE STUDENTS OF AN ACADEMY OF THE ZONE WEST OF THE RIO DE JANEIRO (Fiep Bulletin - online, 2013)
The objective of the study was to verify the profile of the students' of an academy of the Neighborhood of Jacarepaguá percentile of fat, Zone West of Rio de Janeiro. The research was based on Lee (2007), Khol (2007), Hallal et al. (2006), Pollock and Wilmore (1993), Haskell et. al. (2007), among others. The used methodology was descriptive of rising (survey). they Compose the population of the study 158 individuals and the sample belonged to 147 students that accomplished evaluation to begin the program of physical activity in the year of 2006. According to Powers and Howley (2000) they are classified by overweight the percentile ones among 25 and 31,9% of Fat (%G) for women and between 20 and 24,9%G for men. Already the obesity values above 32%G and 25%G, respectively. In agreement with the general averages found the women so much, they are classified inside as overweight and the men of the normality pattern. The results of the study demonstrate that there is an incidence of so much overweight in relation to the feminine general average, as in relation to each age group. In the masculine sample that doesn't happen in the general average, however when treated by age group there is the incidence, although it is not predominant, they are numbers that cannot be despised. The obesity has been pointed as one of the principal problems of world Public Health, therefore it is of fundamental importance that you/they exist public politics that motivate an appropriate feeding and the practice of physical activity to regulate, in order to minimize the action in the health of the populations.
Keywords: Overweight; Obesity; Percentile of fat; Public Health